Effect of the calcination temperature of cerium–zirconium mixed oxides on the structure and catalytic performance of WO3/CeZrO2 monolithic catalyst for selective catalytic reduction of NOx with NH3. Issue 39 (3rd May 2017) - Xu, Haidi; Sun, Mengmeng; Liu, Shuang; Li, Yuanshan; Wang, Jianli; Chen, Yaoqiang
Abstract : The calcined temperature of the carrier obviously affected SCR activity of catalysts, WO3 /Ce0.68 Zr0.32 O2 -500 showed the best low-temperature NH3 -SCR activity due to its more Lewis acid sites and stronger redox property. Abstract : A series of WO3 /CeZrO2 catalysts, prepared at different calcination temperatures (400, 500, 600 and 700 °C) of cerium–zirconium mixed oxides (CeZrO2 ) for the selective catalytic reduction of NO x with ammonia (NH3 -SCR), were investigated via various characterizations, such as N2 physisorption, XRD, Raman, NH3 -TPD, DRIFTS, XPS and H2 -TPR. The catalytic performance of NH3 -SCR was remarkably promoted by modestly increasing the calcination temperature of CeZrO2 : WO3 /CeZrO2 -500 possessed the lowest light-off temperature (173 °C) and complete conversion temperature (205 °C), while W/CeZrO2 -600 could achieve greater than 90% NO x conversion in a broad temperature range of 220–455 °C. The characterization results indicated that modest enhancement of the calcination temperature of CeZrO2 was beneficial to stabilizing the structure of the catalysts. The largest amount of Lewis acid sites, Ce 3+ and surface active oxygen species, as well as strong redox properties of WO3 /CeZrO2 -500 should together contribute to its better low-temperature deNO x activity. Moreover, increasing the calcination temperature of cerium–zirconium mixed oxides resulted in the enhancement of Brønsted acid sites, which was responsible for the widened operation temperature window. Therefore, WO3 /CeZrO2 serial catalysts with appropriate calcination treatment of CeZrO2 would be a good choice for the removal of NO x emitted from diesel engines.